2021
DOI: 10.3390/cancers14010192
|View full text |Cite
|
Sign up to set email alerts
|

A Shortcut from Metabolic-Associated Fatty Liver Disease (MAFLD) to Hepatocellular Carcinoma (HCC): c-MYC a Promising Target for Preventative Strategies and Individualized Therapy

Abstract: Background: Metabolic-associated fatty liver disease (MAFLD) has risen as one of the leading etiologies for hepatocellular carcinoma (HCC). Oncogenes have been suggested to be responsible for the high risk of MAFLD-related HCC. We analyzed the impact of the proto-oncogene c-MYC in the development of human and murine MAFLD and MAFLD-associated HCC. Methods: alb-myctg mice were studied at baseline conditions and after administration of Western diet (WD) in comparison to WT littermates. c-MYC expression was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…According to The Cancer Genome Atlas Research Network, up to 12% of HCC tumors show c‐MYC alterations (“Comprehensive and Integrative Genomic Characterization of Hepatocellular Carcinoma,” 2017). Furthermore, c‐MYC is an attractive target that could guide physicians in adopting preventive strategies and individualized treatment to improve clinical outcomes in metabolic‐associated fatty liver disease‐related HCC (Guo et al., 2021). CASP‐3 plays an important role in apoptosis by inducing proteolytic cleavage of key proteins required for cell function and survival (Lin et al., 2016), and increased CASP‐3 expression and decreased BCL‐2 expression induced apoptosis (Bashir et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to The Cancer Genome Atlas Research Network, up to 12% of HCC tumors show c‐MYC alterations (“Comprehensive and Integrative Genomic Characterization of Hepatocellular Carcinoma,” 2017). Furthermore, c‐MYC is an attractive target that could guide physicians in adopting preventive strategies and individualized treatment to improve clinical outcomes in metabolic‐associated fatty liver disease‐related HCC (Guo et al., 2021). CASP‐3 plays an important role in apoptosis by inducing proteolytic cleavage of key proteins required for cell function and survival (Lin et al., 2016), and increased CASP‐3 expression and decreased BCL‐2 expression induced apoptosis (Bashir et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cancer, MYC was also reported to be involved in the regulation of metabolic diseases, including alcoholic liver disease and NAFLD ( Nevzorova et al, 2016 ), ( Shin et al, 2013 ). Reduced MYC expression increased metabolic activity and reduced cholesterol synthesis in the liver ( Hofmann et al, 2015 ; Luo et al, 2021 ), while overexpression of MYC led to the development of mild steatohepatitis and fibrosis ( Guo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the prevalence of MAFLD has reached pandemic levels, the incidence of MAFLD-related liver fibrosis is increasing ( 9 11 ). At the same time, studies have shown that the progression of liver fibrosis is significantly related to an increased chance of hepatocellular carcinoma (HCC); MAFLD has risen as one of the major causes of HCC ( 12 ); in addition, the increased risk of severe liver-related and cardiovascular events in MAFLD patients is closely related to the fibrotic stage ( 13 ) and is the strongest predictor of mortality in MAFLD patients ( 14 ), so it is crucial to understand the mechanism of MAFLD-related liver fibrosis ( Figure 1 ) and explore effective antifibrotic therapeutic strategies. From metabolic disorders of fatty acids and carbohydrates to persistent liver injury, ultimately leading to liver fibrosis and cirrhosis, the pathogenesis of MAFLD-associated fibrosis relates to many complicated drivers and diverse mechanisms, such as high-concentration hepatic free fatty acid (FFA)-induced mitochondrial dysfunction, oxidative stress, endoplasmic reticulum (ER) stress and inflammation, subsequent hepatocyte apoptosis, and extracellular matrix (ECM) formation, which also involves the interaction of immunity and genetic and epigenetic regulations ( 15 , 16 ).…”
Section: Mafld-related Liver Fibrosis and Its Regression Mechanismmentioning
confidence: 99%